Evaluation of the different inhalational delivery devices techniques among the community pharmacists and general physicians in urban areas in Selangor / Lokman Hakim Abdullah - Abdullah, Lokman Hakim (2013)
The right inhalational delivery devices techniques are vital to ensure the drug particles reached the targeted site to produce desired therapeutic action. These techniques are needed to be equipped among medical related professions especially physicians and pharmacists. This is because they are the front-line health professionals to deal with the patients directly in explaining the correct technique of using various inhalational delivery devices to treat their respiratory diseases especially asthma and chronic obstructive pulmonary disease (COPD). Without respective proper techniques the goals of treatment will not be achieved. The main objective of this study was to determine the demonstration technique level i.e. knowledge level of the community pharmacists and the general physicians regarding their ability to educate patients on how to use the metered dose inhaler (MDI) and dry powder inhalers (DPis) mainly accuhaler and turbuhaler. Post signed consent, the community pharmacists and the general physicians were given questionnaires which consisted of 2 parts: socio-demographic and inhaler's checklist technique. This study recruited 81 community pharmacists and 76 general physicians from various urban areas in Selangor. Data were collected within 4 consecutive months. The overall mean scores of pharmacists for MDI, turbuhaler and accuhaler were 6.67, 6.40 and 5.79, while physicians with 6.96, 6.17 and 5.45, respectively. These were the mean scores for the inhaler techniques which were answered sequentially. There were few significant differences in comparing the level of inhaler techniques with selected socio-demographic data. The results showed that the overall level of knowledge in demonstrating inhaler techniques among the community pharmacists and physicians was moderate (5 - 7 score). Many respondents were unable to obtain excellent score (8 - 10 score). Additional training via continuous professional development programmes should be provided to further equip both respondents with proper inhaler techniques for them to demonstrate the best inhaler techniques to the patients.